The Bangladesh Responsible Sourcing Initiative : A New Model for Green Growth? - World Bank (Washington, DC, 2014)
The objective of this report is to document a new approach to tackle systemic industrial pollution in the textile industry. The Global responsible Sourcing Initiative (RSI) was created in 2010 in response to this challenge. The initiative brings together the World Bank, the International Finance Corporation (IFC), the Natural Resources Defense Council (NRDC), and eight leading multinational brands. This platform allows non-traditional partners to explore a joint approach to address environmental concerns within the global apparel supply chain by collectively changing the business as usual mode of operation.